Pendekatan Perencanaan Strategis Untuk Administrasi Perpajakan Di Rumah Sakit (Studi Kasus RSU Bhakti Yudha Depok Jawa Barat) - Rahman, Abdul (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2009)
Hospital represent one of effort institution which active in service of health. Hospital represent Income Tax (PPh) subject if delivering Goods which is PPN Object than Rp. 600.000.000,-. RSU Bhakti Yudha Depok represent hospital which located in town region of Depok representing region of Dati II. As Subjek of TAX, rsu Bhakti Yudha Depok do obligation of its taxation, among others PPh, PPN and PPh Secction 21 to all itts employees.